Antimicrobial resistance and virulence analysis of Escherichia coli carried by black-faced spoonbill (Platalea minor) in Liaoning, China - Bing Liang; Bo-wen Jiang; Yue Yuan; Tie-cheng Wang; Yuan-guo Li; Ling-wei Zhu; Jun Liu; Xue-jun Guo; Xue Ji; Yang Sun (PLoS ONE, 2026)
To better protect the black-faced spoonbill and explore the transmission and public health risks of drug-resistant pathogenic bacteria carried by this rare migratory bird, 249 fecal samples were collected from the black-faced spoonbills on Shicheng Island, Zhuanghe City, Liaoning Province, China in 2017 and Escherichia coli ( E. coli ) were isolated and identified. The BD Phoenix TM -100 automated microbial identification system and E-test strips were used to determine the resistance phenotype and minimum inhibitory concentration (MIC) value of the isolates. Whole genome sequencing and analysis were conducted on multidrug resistant (MDR) isolates and an evolutionary tree was constructed. Seventy-four samples had E. coli isolated (29.7%), 43.2% of isolates carried an antimicrobial resistant phenotype and 21.6% isolates were considered to be MDR strains. The tetracycline resistance rate was highest (41.9%), followed by ampicillin (20.3%), chloramphenicol (18.9%) and trimethoprim/sulfamethoxazole (17.6%). The highest MIC values of ampicillin, cefazolin, cefotaxime, ciprofloxacin, levofloxacin, and chloramphenicol were eight to 32 times the cutoff point for antimicrobial resistance. Twenty-one types of resistance genes and 35 virulence-associated genes were detected in the MDR isolates and the main type of plasmid was IncFIB. The mcr-1 gene was detected for the first time in MDR E. coli isolated from the black-faced spoonbill. The astA gene was only detected in nine isolates with undetected antimicrobial resistant phenotype. Genetic diversity analysis showed that nine E. coli isolates were mainly concentrated and clustered in independent evolutionary branches in the phylogenetic tree, with serotypes of O-:H8 and the multilocus sequence typing was ST2077, which were in the same evolutionary branch as habitat domesticated animals and environmental isolates. In summary, E. coli may serve as a reservoir of resistance and virulence genes in migratory birds and may be transmitted to other species during migration, with virulent or multidrug resistant E. coli a potential threat to the rare black-faced spoonbill and to human public health.